Knowledge management as an intermediate variable between transformational leadership and administrative empowerment (Case study of the Taif Chamber of Commerce ) - Al-Thaqafi, Ateeq Ali Ahmed (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aimed to knowledge management as an intermediate variable between transformational leadership and administrative empowerment through knowledge of the application of the various processes of knowledge management from diagnosing, generating, storing and applying knowledge, also aimed at identifying the level of transformational leadership with its various variables and administrative empowerment as a variable with transformational leadership and the impact of this on employees Taif Chamber of Commerce. A set of questions and hypotheses has been developed that addressed the problem of the study in its various dimensions. The results showed that the Taif Chamber uses knowledge management by practicing its various operations, which are diagnostic with a mean of 3.93, generation with an average of 3.87, storage with an average of 3.90, and implementation with an average of 3.80. The results also showed a significant relationship at the level of statistical significance (0.05 α ≤) between knowledge management as an intermediate variable between transformational leadership and administrative empowerment. In the light of the results of this study, a set of recommendations was made that enhance knowledge management as an intermediate variable between transformational leadership and administrative empowerment in the Taif Chamber Commercial.
Keywords: knowledge management; administrative empowerment; transformational leadership; Taif Chamber; Saudi Arabia